THE DEVELOPMENT OF THE COMPTROLLER’S SECTION, SADF, 1966-1976 - Bouch, R.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
Introduction: the Secretariat The Comptroller’s Section of the SA Defence Force as it exists today is the inheritor of many of the functions of the civilian Defence Secretariat which was abolished in 1966.